Influence of Design Efficiency of Water Supply Network Inside Building on its Optimum Usage: Review (Journal of Engineering, 2023)
The water supply network inside the building is of high importance due to direct contact with the user that must be optimally designed to meet the water needs of users.  This work aims to review previous research and scientific theories that deal with the design of water networks inside buildings, from calculating the amount of consumption and the optimal distribution of the network, as well as ways to rationalize the use of water by the consumer.  The process of pumping domestic water starts from water treatment plants to be fed to the public distribution networks, then reaching a distribution network inside the building till it is  provided to the user.  The design of the water supply network inside the building is mainly affected by the amount of water consumed in the building. On this basis, the pipes' dimensions and the water tank's volume are determined. The operating pressure of the water supply network inside the building is calculated to overcome the height difference and the friction inside the pipes and provide sufficient pressure to operate the most remote fixture.  The most important results of the research are that the optimal use of the water distribution network inside the buildings is achieved by the correct design and implementation using skilled labor, materials, and devices of high quality and rationalization of water consumption by the user.